Investigation on the peak temperature and surface defects on the carbon steel treated by rotating CW laser. (March 2021) - Zhuang, Shusen; Kainuma, Shigenobu; Yang, Muye; Haraguchi, Manabu; Asano, Takahiro
Highlight: A newly developed rotating CW laser is adopted as a surface cleaning method. Surface defects could be induced by frequent overlapping of laser beam. Re-melted zone of laser-treated specimens are well described by peak temperature distribution. Modified analytical method for peak temperature distribution is expected to optimize processing parameters. Abstract: A newly developed rotating continuous-wave laser equipment was adopted as an alternative laser-based surface cleaning method. To evaluate the thermal effects of laser cleaning on base material, a modified calculation method for laser-induced peak temperature distribution considering overlapping effects was proposed. Various laser-processing parameters were adopted to irradiate carbon steel plates. The re-melted zone (MZ) of laser-treated specimens was observed under optical microscopy and used to verify the calculation method. Surface morphologies and roughness of laser-treated specimens were also investigated. The results showed that the peak temperature distribution obtained from the modified calculation method properly describes the MZ depth in laser-treated specimens. Investigation on laser-treated specimens revealed that results of laser heat effects improved in rougher surface conditions, and that frequent overlapping of laser beam can induce surface defects. The modified calculation method could help to optimize laser processing parameters to reduce melting of base material and avoid surface defects.